PEACEFUL JIHÄD DAN PENDIDIKAN DERADIKALISASI AGAMA - Sulasman, Sulasman (WALISONGO, 2015)
The Islamic Boarding School (Pondok Pesantren) Miftahul Huda was originatellyidentical with the radicalism movement not only because of its exclusivism in religiousactivities, the criticism toward the government, but also the identification of itsmembers with DI/TII movement and FPI. In line with internal and external dynamics,this boarding school reoriented its movement from physical jihÄd to the path ofeducation and peaceful dakwah or in Lukens-Bullâs perspective it is so-called peacefuljihÄd. The process of self-domestication and the movement of de-radicalization in thisboarding was executed by six ways. They are internalizing the values of boardingschool, increasing the Islamic perspective, adopting schools system, providing theeducation of hubb al-waá¹an, using local wisdom, and developing skill education. Thestrategy of de-radicalization applied by Miftahul Huda Islamic Boarding School isdivided into three efforts; preventive de-radicalization, preservative de-radicalization,and curative de-radicalization. The results was shown that the students, alumni, andthe boarding schools incorporated in Miftahul Huda Islamic boarding schoolnetworking system that appears in peace, moderate, and tolerance appearance.***Pondok Pesantren Miftahul Huda semula identik dengan gerakan âradikalâ baikkarena pandangan eksklusivismenya dalam beragama, kritisisme terhadapPemerintah, maupun karena keidentikkan beberapa personalnya dengan gerakanDI/TII dan FPI. Sejalan dengan dinamika internal dan eksternal, pondok pesantrenini pun mereorientasi gerakannya dari jihÄd fisik ke jalur pendidikan dandakwah damai atau dalam perspektif Lukens-Bull dikenal sebagai jihad damai(peaceful jihÄd). Proses menjinakkan diri dan gerakannya, yang dikenal denganderadikalisasi, dilalui oleh pondok pesantren ini dengan enam cara, yakni internalisasinilai-nilai pesantren, perluasan perspektif keislaman, adopsi sistemsekolah, pendidikan hubb al-waá¹an, penggunaan local wisdom, dan pendidikanketerampilan. Upaya deradikalisasi yang dilakukan Pondok Pesantren MiftahulHuda berkisar pada tiga strategi, yakni pencegahan, pemeliharaan budaya damai,dan pemulihan bagi yang terdampak radikal. Hasilnya, para santri, alumni, danpesantren yang tergabung dalam sistem jaringan Pondok Pesantren MiftahulHuda muncul dalam wajah damai, moderat, dan toleran.